2012
DOI: 10.1177/2040620712458949
|View full text |Cite
|
Sign up to set email alerts
|

Alemtuzumab use in relapsed and refractory chronic lymphocytic leukemia: a history and discussion of future rational use

Abstract: Abstract:In this review, we outline the clinical experience with single-agent alemtuzumab as a treatment for relapsed and refractory chronic lymphocytic leukemia (CLL) in both prospective and retrospective trials and describe the multiagent use of the drug with the goal of updating clinicians on recent developments and possible future rational combinations. Alemtuzumab, an antibody targeting the lymphocyte-specific surface marker CD52, is an approved agent for the treatment of CLL. Despite its demonstrated eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 96 publications
0
14
0
1
Order By: Relevance
“…GO and alemtuzumab also counteracted engraftment of LSCs in NSG mice. However, these drugs also produce cytopenia and, thus, hematologic toxicity, 80,81 because CD33 and CD52 are also expressed on normal HSCs. Therefore, the dose of these antibody conjugates may play a decisive role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GO and alemtuzumab also counteracted engraftment of LSCs in NSG mice. However, these drugs also produce cytopenia and, thus, hematologic toxicity, 80,81 because CD33 and CD52 are also expressed on normal HSCs. Therefore, the dose of these antibody conjugates may play a decisive role.…”
Section: Discussionmentioning
confidence: 99%
“…One is that LSCs in AML and CML exhibit subclone-specific heterogeneity; therefore, not all LSCs in a given neoplasm may express the same targets. 17,81,84,85 Rather, smaller subsets of LSCs may lack certain targets, and these cells may survive therapy. In addition, LSCs may exhibit intrinsic resistance and escape toxin conjugate-based therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The biotherapeutic is directed against CD52 cells and is approved for the intravenous treatment of chronic lymphocytic leukemia. Small pilot studies using subcutaneous infusion reported that immediate flu-like toxicities associated with intravenous treatment were less severe when using the subcutaneous route of administration [ 80 ]. Furthermore, acute subcutaneous IRRs, such as rigor, rash or urticaria, nausea, hypotension, or bronchospasm, were rare or absent in contrast to the observations previously made for intravenous infusions [ 81 ].…”
Section: Pharmacokinetic Differences Between Intravenous and Subcutanmentioning
confidence: 99%
“…However, in clinical practice, such associations are far from deterministic because they are modulated by a plethora of factors, such as the nature and stage of the underling condition, the prior or concurrent receipt of other immunosuppressive agents, the duration of therapy or the accumulative exposure to the agent. This concept is well exemplified by the notable differences in the rates of infection observed with the use of the anti-CD52 mAb alemuzumb according to the indication of therapy, multiple sclerosis or B-cell malignancy (because the corresponding maximum annual doses vary from 36 to 1080 mg respectively) [53,54]. In the case of immune checkpoint inhibitors targeting inhibitory T-cell receptors, such as nivolumab or ipilimumab, the risk is not driven by the use of the agent itself but by the subsequent requirement of additional immunosuppression therapy to manage the immune-related adverse effects emerging from the upregulation of immune response [55].…”
Section: Assessment Of Infection Risk: From Molecule To Bedsidementioning
confidence: 99%